2017
DOI: 10.1111/eve.12777
|View full text |Cite
|
Sign up to set email alerts
|

Management of equine ataxia caused by cervical vertebral stenotic myelopathy: A European perspective 2010–2015

Abstract: Summary The diagnosis and therapy of cervical vertebral stenotic myelopathy (CVSM) are challenging and have been most frequently described in racehorses. We aimed to analyse CVSM cases presented for diagnostic work‐up and treatment in a nonracing horse population. We hypothesised that our diagnostic work‐up protocol including clinical/orthopaedic/neurological/radiographic and myelographic examinations may provide practical reference points for in vivo diagnosis/prognosis and adequate CVSM management. Medical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…The PRE stallion’s neck is usually more voluminous, and stallions are used for sport more often than PRE mares. Another cervical disease, stenotic myelopathy, has been studied previously and its prevalence was also higher in stallions than in females [ 34 ]. Age also was a relevant risk factor for Ewe Neck, with young horses (4–7 years old) showing higher percentages of those affected.…”
Section: Discussionmentioning
confidence: 99%
“…The PRE stallion’s neck is usually more voluminous, and stallions are used for sport more often than PRE mares. Another cervical disease, stenotic myelopathy, has been studied previously and its prevalence was also higher in stallions than in females [ 34 ]. Age also was a relevant risk factor for Ewe Neck, with young horses (4–7 years old) showing higher percentages of those affected.…”
Section: Discussionmentioning
confidence: 99%
“…3 Similarly, another recent study found single-level stenosis in 37%, double-level stenosis in 35% and triple-level stenosis in 13% of their patients examined myelographically during the diagnostic work-up of suspected CVSM. 4 The most frequent combination of double-level stenosis is CV 3 to 4 and CV 5 to 6 followed by CV 3 to 4 and CV 4 to 5. 3 Additionally, recent studies emphasize the benefits of advanced imaging techniques such as computed tomography (CT) or magnetic resonance imaging over plain radiographs.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] Although CVSM is described in almost all horse breeds, Thoroughbreds, Warmbloods and Tennessee Walking Horses appear to be more frequently affected. 1,4 The diagnosis requires a detailed patient history, physical and neurological examination as well as diagnostic imaging. 5 Evaluation of plain radiographs in combination with calculation of the intra-and intervertebral minimal sagittal ratios or diameter can initially raise a valid suspicion of CVSM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations